2013
DOI: 10.1021/ol400542b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Unsymmetrical Azomethine Imines Formed Using Alkene Aminocarbonylation

Abstract: Complex cyclic azomethine imines possessing a β-aminocarbonyl motif can be accessed readily from simple alkenes and hydrazones. This alkene aminocarbonylation approach allows formation of ketone-derived azomethine imines of unprecedented complexity. Since unsymmetrical hydrazones are used, two stereoisomers are formed: the reactivity of chiral derivatives is explored in both intra- and intermolecular systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 28 publications
(9 reference statements)
2
45
0
Order By: Relevance
“…Evaporation of solvent gave the desired product (1.21g, 98%) as a white solid. Rf 0.4 (100% CH2Cl2); Phenyl 2-(thiophen-2-ylmethylene)hydrazinecarboxylate (4j -substrate for Figure 24) Synthesized according to literature, 65 with minor modifications. Phenyl carbazate (0.304 g, 2.00 mmol), thiophene-2-carbaldehyde (0.224 g, 2.00 mmol), acetic acid (0.04 mL) and methanol (5 mL) were combined and left to stir for 1 h at room temperature.…”
Section: Phenyl 2-(4-(trifluoromethyl)benzylidene)hydrazinecarboxylatmentioning
confidence: 99%
“…Evaporation of solvent gave the desired product (1.21g, 98%) as a white solid. Rf 0.4 (100% CH2Cl2); Phenyl 2-(thiophen-2-ylmethylene)hydrazinecarboxylate (4j -substrate for Figure 24) Synthesized according to literature, 65 with minor modifications. Phenyl carbazate (0.304 g, 2.00 mmol), thiophene-2-carbaldehyde (0.224 g, 2.00 mmol), acetic acid (0.04 mL) and methanol (5 mL) were combined and left to stir for 1 h at room temperature.…”
Section: Phenyl 2-(4-(trifluoromethyl)benzylidene)hydrazinecarboxylatmentioning
confidence: 99%
“…4) by the reaction of hydrazone derivatives 113 bearing ester or amide moieties at the N-atom with alkenes (aminocarbonylation) in the absence of a solvent or in a,a,a-trifluorotoluene (Scheme 46). 144,149,150 The generation of N,N H -cyclic azomethine imines from hydrazones and alkenes is a thermal concerted reaction proceeding via the formation of an imino isocyanate intermediate the existence of which was confirmed by quantum chemical calculations. 150 …”
Section: Methods For Generation Of Azomethine Imines and Their 1mentioning
confidence: 85%
“…142,149 Apparently, this reaction initially occurs to form the azomethine imine 157, the Z-isomer of which is further transformed into the cyclopenta [4,5] …”
Section: Scheme 65mentioning
confidence: 99%
“…In contrast to normal ( C ‐substituted) isocyanates, the reactivity of N ‐substituted isocyanates has received little attention from the synthetic community 5. Recently, we reported that amphoteric amino‐ and imino‐isocyanates can be formed in situ under mild conditions and engage in high‐yielding alkene cycloadditions6ac and nucleophilic additions,6d,e despite their known tendency to dimerize or oligomerize 7. 8 Hydrazones6bd and hydrazides6a,e are bench‐stable, convenient “blocked” N ‐substituted isocyanate precursors9 that form the desired isocyanates via an equilibrium induced under mild conditions, and then react with nucleophiles such as amines, alcohols, and thiols 6de.…”
Section: Methodsmentioning
confidence: 99%